Negotiating Patriarchal Relationship: Representation of Subjectification in Doja Cat’s Woman (2021) Music Video - Afriano, Reno; Hapsari, Nurul Fitri; Puspita, Yulia Mega; Tiantini, Wendy Belinda (Journal of Language and Literature, 2024)
This study aims to illustrate the subjectification of women's bodies as one of the notions of postfeminist sensibility. Subjectification involves depicting women in a patriarchal setting as empowered individuals with agency, highlighting their reservoirs of strength and spheres of influence, challenging the perception of complete powerlessness. The object of investigation in this study is the music video by Doja Cat entitled "WOMAN" (2021), with a primary focus on examining the dynamic interaction among female talents within the context of the surrounding characters and environment. The author employs textual and visual analysis with qualitative methods and Fiske's Television Culture. In terms of theory, the analysis of the objects was supported by drawing upon Rosalind Gill's postfeminist sensibility. The study's analysis reveals that female talents, initially characterized by power and agency, faces a threat in the presence of patriarchy. This compels them to leverage their bodies and traditional roles as tools for negotiation. This study finds out that subjectification also can be an effort for women to negotiate patriarchal relationships as the bodies were used as tools to assert control and authority over the opposite sex without engaging as an object instead as a subject. This also counters the typical male gaze that makes women look passive or disempowered.